2018
DOI: 10.1038/s41398-018-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects on gene expression and behavior of untagged short tandem repeats: the case of arginine vasopressin receptor 1a (AVPR1a) and externalizing behaviors

Abstract: Genome-wide association studies (GWAS) of complex, heritable, behavioral phenotypes have yielded an incomplete accounting of the genetic influences. The identified loci explain only a portion of the observed heritability, and few of the loci have been shown to be functional. It is clear that current GWAS techniques overlook key components of phenotypically relevant genetic variation, either because of sample size, as is frequently asserted, or because of methodology. Here we use arginine vasopressin receptor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…1214,32 Other approaches (e.g., genome-wide association studies) have clear benefits, although we note that they typically do not assess tandem repeat genetic variants, such as 5-HTTLPR. 40…”
Section: Discussionmentioning
confidence: 99%
“…1214,32 Other approaches (e.g., genome-wide association studies) have clear benefits, although we note that they typically do not assess tandem repeat genetic variants, such as 5-HTTLPR. 40…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in many cases single genes have very small effect sizes (for review, see Fox and Beevers, 2016). However, GWAS studies are limited in that they require very large sample sizes (Landefeld et al, 2018). Other important genetic variants may also be examined in future studies, for example, the 5-HTTLPR VNTR of the serotonin transporter gene that has been associated with differences in life history strategy and risk-acceptance in mating competition (Minkov and Bond, 2015).…”
Section: Future Directions and Limitationsmentioning
confidence: 99%
“…For example, copy-number variants and expansions and contractions of micro-and mini-satellite sequences can be difficult to identify with short-read or Sanger sequencing technologies. Nevertheless, these types of mutations have been implicated in a wide range of neurological diseases, including Huntington disease, spinocerebellar ataxia, fragile X syndrome, depression, and aggression and impulsivity behaviors, [33][34][35][36][37][38][39][40] and likely contribute to undetected variation and missing heritability for additional human traits. 41,42 To search for unrecognized copy-number variants at the CACNA1C locus, we examined regions of the genome where no mutations were identified by large-scale sequencing projects such as the 1000 Genomes Project, 43 yet DNA sequencing reads consistently differed from the reference human assembly.…”
mentioning
confidence: 99%